The Debate Between Customary Traditions and Islamic Family Law: Parental Dominance in Arranged Marriages Following Divorce in Pangkep - Al Bahri, Ulil Azmi; Agus Muchsin; Zainal Said (Al-Iftah: Journal of Islamic studies and society, 2025)
This study aims to examine the phenomenon of parental dominance in the practice of arranged marriages, specifically in the context of divorces resulting from such arrangements in Ma’rang District, Pangkep Regency. Employing a qualitative approach with a case study design, this research collects primary data from parents who have arranged marriages for their children, individuals who were involved in arranged marriages, religious leaders, and community figures. Secondary data were obtained from scholarly literature discussing similar themes. Data collection techniques include observation, in-depth interviews, and documentation. The analysis framework is built upon domination theory, conflict theory, and the concept of maqāṣid al-sharī‘ah. The findings indicate that parents exercise dominance through three approaches: persuasive, authoritative, and coercive. This dominance has significant implications, including marital disharmony, psychological distress, divorce, post-marriage trauma, and interfamily conflict. From the perspective of Islamic family law, arranged marriages that exclude the children's consent are inconsistent with the core values of maqāṣid al-sharī‘ah—specifically the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), and progeny (ḥifẓ al-nasl). It also violates Article 16 (1) and (2) of the Compilation of Islamic Law, which mandates the mutual consent of both parties in a marriage contract. Based on these findings, the study recommends that family decision-making processes prioritize open dialogue and individual autonomy in order to build marriages that reflect Islamic ideals of sakinah, mawaddah, and rahmah. In addition, the study encourages policymakers and religious authorities to strengthen community awareness regarding the legal and ethical dimensions of marriage decisions.